2013
DOI: 10.1371/journal.pone.0078812
|View full text |Cite
|
Sign up to set email alerts
|

Nodular Lymphocyte Predominant Hodgkin Lymphoma and T Cell/Histiocyte Rich Large B Cell Lymphoma - Endpoints of a Spectrum of One Disease?

Abstract: In contrast to the commonly indolent clinical behavior of nodular lymphocyte predominant Hodgkin lymphoma (NLPHL), T cell/histiocyte rich large B cell lymphoma (THRLBCL) is frequently diagnosed in advanced clinical stages and has a poor prognosis. Besides the different clinical presentations of these lymphoma entities, there are variants of NLPHL with considerable histopathologic overlap compared to THRLBCL. Especially THRLBCL-like NLPHL, a diffuse form of NLPHL, often presents a histopathologic pattern simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 54 publications
2
43
0
1
Order By: Relevance
“…Gene expression analysis was performed and analyzed as previously described [11, 12]. Gene expression data are available through the GEO database (GEO accession number GSE86477).…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression analysis was performed and analyzed as previously described [11, 12]. Gene expression data are available through the GEO database (GEO accession number GSE86477).…”
Section: Methodsmentioning
confidence: 99%
“…The 2008 WHO classification recommended describing NLPHL cases that progressed to a diffuse T-cell-rich pattern as ‘THRLBCL-like NLPHL’ to distinguish them from primary THRLBCL and indicated that at least focal presence of a typical NLPHL nodule be required for the diagnosis of NLPHL [1,2,80]. In the 2016 revision of the WHO classification, these cases are designated ‘THRLBCL-like transformation of NLPHL’ and have a more aggressive clinical course than typical NLPHL [2,85,86]. …”
Section: Hodgkin Lymphomasmentioning
confidence: 99%
“…In line with these data, studies of gene expression profile (GEP) carried on isolated neoplastic cells indicate that LP cells possibly originate from germinal center B cells at the transition to memory B cells. Recently, using the same approach, Hartmann et al performed GEP of microdissected tumour cells of NLPHL, THRLBCL-like NLPHL and THRLBCL and interestingly in unsupervised analyses, the examples of the three types of lymphoma did not form separate clusters 17. Moreover, even in supervised analyses, very few consistently differentially expressed transcripts were found, and for these genes the extent of differential expression was only moderate.…”
Section: Nodular Lymphocyte Predominant Hodgkin Lymphomamentioning
confidence: 99%